2022
DOI: 10.3390/agronomy12020368
|View full text |Cite
|
Sign up to set email alerts
|

Cattle Manure Fermented with Biochar and Humic Substances Improve the Crop Biomass, Microbiological Properties and Nutrient Status of Soil

Abstract: Co-composting of raw manure with other organic sources has recently gained the attention of the scientific community. In the present study, raw manure and manures enriched with humic substances (Humac) or biochar were co-composted to improve their physico-chemical properties. We conducted an experiment including variants consisting of soil amended with manure (M), manure + Humac (M + H), manure + biochar (M + B), and unamended (control). Soil physico-chemical, biological, and plant properties were assessed alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The enzymes related to N cycling tended to increase in activities following the application of C‐rich amendments, which was consistent with previous observations (Antonious et al., 2020; Asirifi et al., 2021; Holatko, Bielska, et al., 2022; Sekaran et al., 2020). It is known that when high C contents are added to the soil, such as when organic amendments were added here, microorganisms need to consume more N to balance their resources, and thus N‐related enzymes increased (Asirifi et al., 2021; Foster et al., 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The enzymes related to N cycling tended to increase in activities following the application of C‐rich amendments, which was consistent with previous observations (Antonious et al., 2020; Asirifi et al., 2021; Holatko, Bielska, et al., 2022; Sekaran et al., 2020). It is known that when high C contents are added to the soil, such as when organic amendments were added here, microorganisms need to consume more N to balance their resources, and thus N‐related enzymes increased (Asirifi et al., 2021; Foster et al., 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Since farmers are storing manure outside for the entire growing seasons, loss of nutrients can already occur during that period and thus the incorporation of biochar before, such as when manure is heaped outside, could help maintain the fertility of manure over a longer period, though there is a paucity of evidence in this regard (Lebrun et al., 2022). Both amendments also have benefits for soil microorganisms, generally increasing their activity and diversity (Hammerschmiedt et al., 2022; Holatko, Bielska, et al., 2022; Song et al., 2019; Sun et al., 2014), which is crucial for soil fertility. Indeed, soil microorganisms play an important role in SOM and nutrient cycling (Garbowski et al., 2023) and in the transformation of nutrients from organic to mineral forms available for plants (Ahmad et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil chemical and physico-chemical properties are important determinants of soil quality. It has been shown that biochar application results in the modification of soil chemical properties mainly pH and electrical conductivity and soil nutrient status ( Joseph et al., 2020 ; Holatko et al., 2022 ). We found enhanced soil pH under the application of food waste biochar (FWB) with and without MF ( Figure 2A ).…”
Section: Discussionmentioning
confidence: 99%
“…Manure methane fermentation is usually quite uniform and takes about 20-24 days. The length of the fermentation process normally depends on the production technology, the type and method of laying the litter [71] and the way of feeding the animals (type of diet) [72]. However, the resulting product conventionally has a similar composition and is characterized by a high content of organic matter and nutrients.…”
Section: Emission and Energy Calculations For Scenario IImentioning
confidence: 99%